Kill all enemies - Burgess, Melvin (London : Penguin Books, 2011)
Everyone says fourteen-year-old BILLIE is nothing but trouble. A fighter. A danger to her family and friends. But her care worker sees someone different.Her classmate ROB is big, strong; he can take care of himself and his brother.But his violent stepdad sees someone to humiliate.And CHRIS is struggling at school; he just doesn't want to be there.But his dad sees a useless no-hoper.Billie, Rob and Chris each have a story to tell. But there are two sides to every story, and the question is . . . who do you believe?